Evaluasi Kondisi Pariwisata Kawasan Wisata Gunung Galunggung - Dofi khaikal Arwani; Gina Puspitasari Rochman (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. The tourist area of Mount Galunggung is one of the leading natural tourist areas in Tasikmalaya Regency. This area will be developed into a geotourism area. Prior to development, it is necessary to evaluate the tourism condition in this area. This is because there are several problems that exist in the Mount Galunggung tourist area including the discovery of a large amount of garbage scattered about, the existence of vandalism by visitors, accessibility to the damaged Galunggung crater, and things that worsen the tourism situation due to the Covid-19 pandemic which resulted in the closure of the Mount Galunggung tourist area for some time and caused considerable losses for the tourist area. Therefore, the purpose of this study is "to assess the feasibility of tourism conditions in the Mount Galunggung tourist attraction area during the covid 19 pandemic". This is based on theories and policies regarding evaluation, tourists, tourist objects and attractions and tourism components. The existence of this theory so that researchers use a quantitative and qualitative approach to determine a hypothesis test that has been determined. With scoring analysis method and data testing method, namely normality test, validity test, and reliability test. Therefore, the conclusion of this study is that the components of tourist attractions (Attraction), amenities (amenities), accessibility (accessibility), and tourism support (Ancilliary Services) in the Galunggung Tourism Area are in good condition based on tourist ratings. With that, there are suggestions from researchers, namely improving the condition of the tourism component, building lodging around tourist areas, increasing the application of Health protocols, and increasing promotion and information media. Abstrak. Kawasan wisata gunung galunggung adalah salah satu Kawasan wisata alam unggulan di Kabupaten Tasikmalaya. Kawasan ini akan dikembangkan menjadi Kawasan geowisata. Sebelum dilakukan pengembangan, diperlukan adanya suatu evaluasi kndisi pariwisata di Kawasan ini. Hal ini dikarenakan terdapat beberapa permasalahan yang ada dikawasan wisata gunung galunggung diantaranya ditemukan banyaknya sampah yang berserakan, adanya vandalism yang dilakukan oleh para pengunjung, aksesibilitas menuju ke kawah galunggung yang rusak, serta hal yang memperburuk keadaan wisata tersebut karena adanya pandemi Covid-19 yang berakibat pada ditutupnya Kawasan wisata Gunung Galunggung selama beberapa waktu dan menyebabkan kerugian yang cukup besar bagi kawasan wisata tersebut. Maka dari itu tujuan dalam penelitian ini yaitu “Untuk mengevaluasi kondisi pariwisata di Kawasan objek wisata Gunung Galunggung”. Hal tersebut didasari dengan teori serta kebijakan mengenai evaluasi, wisatawan, objek dan daya tarik wisata serta komponen wisata. Adanya teori tersebut sehingga peneliti menggunakan metode pendekatan kuantitatif dan kualitatif untuk menentukan suatu uji hipotesis yang sudah ditetapkan. Dengan metode analisis skoring serta metode pengujian data yaitu uji normalitas, uji validitas, dan uji reliabilitas. Maka dari itu kesimpulan dari penelitian ini yaitu Komponen atraksi wisata (Attraction), Amenitas (amenities), Aksesibilitas (accessibility), dan pendukung wisata (Ancilliary Services) di Kawasan Wisata Galunggung berada dalam kondisi baik berdasarkan penilaian wisatawan. Dengan itu adanya usulan dari peneliti yaitu peningkatan kondisi komponen wisata, pembangunan penginapan di sekitar kawasan wisata, peningkatan penerapan protokol Kesehatan, dan peningkatan media promosi dan informasi.